2022
DOI: 10.3390/polym14142880
|View full text |Cite
|
Sign up to set email alerts
|

The Variance of Photophysical Properties of Tetraphenylethene and Its Derivatives during Their Transitions from Dissolved States to Solid States

Abstract: The study of aggregation-induced emission luminogens (AIEgens) shows promising perspectives explored in lighting, optical sensors, and biological therapies. Due to their unique feature of intense emissions in aggregated solid states, it smoothly circumvents the weaknesses in fluorescent dyes, which include aggregation-caused quenching of emission and poor photobleaching character. However, our present knowledge of the AIE phenomena still cannot comprehensively explain the mechanism behind the substantially enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Figure 5c shows the changes in the PL spectra of aqueous solutions of TPE-C(4)N + Me 3 Br − with the addition of Fenton's reagent. The computational calculations revealed that the PL peaks of TPE at 459 nm and 540 nm corresponded to the S 3 → S 0 and S 1 → S 0 transitions, respectively [33]. As shown in Figure 5c, the peak at approximately 470 nm, which corresponds to S 1 → S 0 transition, disappeared with the addition of four equimolar amounts of Fenton's reagent.…”
Section: Hydroxyl Radical Sensingmentioning
confidence: 90%
“…Figure 5c shows the changes in the PL spectra of aqueous solutions of TPE-C(4)N + Me 3 Br − with the addition of Fenton's reagent. The computational calculations revealed that the PL peaks of TPE at 459 nm and 540 nm corresponded to the S 3 → S 0 and S 1 → S 0 transitions, respectively [33]. As shown in Figure 5c, the peak at approximately 470 nm, which corresponds to S 1 → S 0 transition, disappeared with the addition of four equimolar amounts of Fenton's reagent.…”
Section: Hydroxyl Radical Sensingmentioning
confidence: 90%
“…Generally, the AIEgens are typically built in the π -conjugated molecular architectures with a lot of branching groups to prevent fluorescence quenching in aggregated states. [22][23][24][25] Additionally, the expanded π -conjugated molecular structures are commonly believed to produce the emission with a longer wavelength (lower energy), which can be used to modify the emission wavelength of AIEgens. [26][27][28][29] The optical behaviors ofπ -conjugated AIEgens, however, are considerably more complex and do not simply follow this empirical principle.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the AIEgens are designed in the π -conjugated molecular structures with a lot of branched groups to prevent fluorescent quenching in aggregated states. [32][33][34][35][36][37][38] In addition, to adjust the emission wavelength of AIEgens, the expanded π -conjugated molecular structures are commonly believed to result in the emission with a longer wavelength (lower energy). [39][40][41][42] However, the optical behaviors of π -conjugated AIEgens perform much more complicated and do not simply follow this empirical principle.…”
Section: Introductionmentioning
confidence: 99%